A new species from India with a key to all known species of the genus Anaptygus Mistshenko, 1951 (Orthoptera: Acrididae) - Kumar, Hirdesh; Chandra, Kailash; Saini, Jagdish (Zootaxa, 2020)
A new species of the genus Anaptygus Mistshenko, 1951, Anaptygus shishodiai Kumar & Chandra sp. nov., from Valley of Flowers National Park, India is described in this paper. The new species is similar to A. qinghaiensis Yin, 1984, but differs from latter by length of fastigial foveolae 5.5 times its width in male and 3.2 times in female; apex of elytra reaching posterior margin of third abdominal tergite in male and reaching posterior margin of first abdominal tergite in female. A key to all the known species of Anaptygus Mistshenko, 1951 is also provided.